Day-night oscillations of cognitive functions, TNF alpha and clock -related factors expression are modified by an intracerebroventricular injection of amyloid beta peptide in rat. (March 2022) - Ledezma, Carina; Coria-Lucero, Cinthia; Castro, Andrea; Leporatti, Jorge; Perez, Mariela; Delgado, Silvia; Anzulovich, Ana Cecilia; Navigatore-Fonzo, Lorena
Abstract: Alzheimer's disease (AD) is the most common form of dementia characterized by a gradual impairment in cognitive functions. Recent research have shown that TNF-α is a proinflammatory cytokine implicated in the pathogenesis of neurodegenerative diseases, such as AD. Besides cognitive deficit, AD patients show alterations in their circadian rhythms. The objective of this work was to investigate the effects of an intracerebroventricular injection of Aß aggregates on temporal patterns of cognitive functions and on daily rhythms of Aβ, TNFα, BMAL1 and RORα protein levels in the rat prefrontal cortex. Four-month-old males Holtzman rats were used in this study. Groups were defined as: control and Aβ-injected rats. Rats were maintained under 12h-light:12h-dark throughout the entire experimental period. Prefrontal cortex samples were isolated every 4 h during a 24h period. Our results demonstrated that an intracerebroventricular injection of Aß aggregates impaired learning and memory in rats at ZT 2 and ZT 14 and modified daily patterns of Aβ, TNFα, and clock-related factors in the rat prefrontal cortex. Our findings showed that the increase of Aß altered temporal patterns of TNFα, and, consequently, induced alterations in daily rhythms of clock-related factors, affecting the cognitive performance of animals with Alzheimer's. Highlights: Daily rhythms of TNFα and clock-related factors are observed in the rat prefrontal cortex. Temporal patterns of cognitive functions are found in this brain area. An injection of Aβ aggregates phase shifted daily rhythms of TNFα, BMAL1 and RORα. The Aβ group showed alterations in cognitive functions.